2013
DOI: 10.1016/j.agwat.2013.06.008
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of the water stress effects on peach fruit quality and size using a fruit tree model, QualiTree

Abstract: Research highlights:-A middle-late maturing peach cultivar was successfully implemented into QualiTree.-QualiTree was able to adequately simulate the effects of water stress on fruit growth.-Fructose, glucose and sorbitol contents in the fruit flesh were well simulated.-Water stress increased sugar contents in the fruit flesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 47 publications
2
16
1
Order By: Relevance
“…In our trials, after a decrease in 60% of the water supply throughout plant growth, we observed on average reduced plant vigor and yield, while fruit quality was improved or stable depending on whether metabolite concentrations were expressed relative to FM or DM. This antagonistic relationship between quality and yield performances confirmed the results obtained in RILs (Albert et al , 2016) and the tendencies reported by other authors in tomato (Guichard et al , 2001; Kirda et al , 2004; Zheng et al , 2013), peach (Mirás-Avalos et al , 2013), or grapevine (Santesteban and Royo, 2006). …”
Section: Discussionsupporting
confidence: 90%
“…In our trials, after a decrease in 60% of the water supply throughout plant growth, we observed on average reduced plant vigor and yield, while fruit quality was improved or stable depending on whether metabolite concentrations were expressed relative to FM or DM. This antagonistic relationship between quality and yield performances confirmed the results obtained in RILs (Albert et al , 2016) and the tendencies reported by other authors in tomato (Guichard et al , 2001; Kirda et al , 2004; Zheng et al , 2013), peach (Mirás-Avalos et al , 2013), or grapevine (Santesteban and Royo, 2006). …”
Section: Discussionsupporting
confidence: 90%
“…One of the benefits of RDI is an improvement in fruit taste and quality due to increasing SSC (Mpelasoka et al, 2000;López et al, 2011;Mirás-Avalos et al, 2013). In the present study, SSC values increased in all years for the RDI treatment although this difference was significant only in 2008, when a higher level of water stress was observed.…”
Section: Discussioncontrasting
confidence: 41%
“…A comprehensive description of QualiTree can be found in Lescourret et al ( 2011 , 2016 ). Parameters and validations for several peach cultivars are reported in Mirás-Avalos et al ( 2011 , 2013a , b ). A list of QualiTree inputs and outputs is provided in Supplementary Tables 1 , 2 .…”
Section: Methodsmentioning
confidence: 99%
“… Ranges of values for these parameters found in the literature are also shown. Ranges for the different parameters were taken from Harrison et al ( 1989 ), Lescourret and Génard ( 2005 ), Mirás-Avalos et al ( 2011 , 2013a , b ), and Wu et al ( 2012 ) . …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation